Fermentation of kefir with traditional freeze-dried starter cultures successfully recreates fresh culture fermented kefir - Mudoor Sooresh, Maanasa; Jayawickrama, Ashani; Silva, Amaya; Nguyen, Sally; Schmidt, Sheri; Sebastian, Joseph; Carey, Shane; Harynuk, James; Willing, Benjamin P.; Bourrie, Benjamin C. T. (Frontiers in Microbiology, 2025)
IntroductionInterest in fermented foods and their purported health benefits has led to increased scientific research investigating the development of starter cultures which maintain the characteristics of traditional products while allowing for industrial scale production. One such fermented food that is gaining steady attention for industrial production is kefir. To improve the ease of use and maintenance of starter cultures without compromising desirable fermentation characteristics and potential health benefits, this study investigated the impact of freeze-drying a previously described reconstituted kefir consortia with two lyoprotectants trehalose and milk.Methods5 bacterial species (Lentilactobacillus kefiri, Lactobacillus kefiranofaciens, Lactococcus cremoris, Leuconostoc mesenteroides, and Acetobacter pasteurianus) and 4 yeast species (Saccharomyces cerevisiae, Pichia fermentans, Monosporozyma unispora, and Kluyveromyces marxianus) underwent freeze-drying prior to viability testing and use as starter cultures in kefir fermentations. Completed kefir fermentations were analyzed for pH, microbial composition, volatile compounds, organic acids, and sugar consumption. Freeze-dried starter culture fermentations were compared to kefir made with fresh starter cultures of the same species and pitching rate.ResultsAll starter cultures were able to ferment milk to a similar pH, however the freeze-dried cultures prepared with milk took a longer time to complete fermentation. The total bacterial and yeast counts were comparable across the fermentations performed as was the composition of bacteria and yeast present as determined by shotgun metagenomic sequencing. High performance liquid chromatography (HPLC) analysis showed no difference in the levels of lactic acid, acetic acid, ethanol, glucose, and galactose. Additionally, solid-phase microextraction followed by two-dimensional gas chromatography-time-of-flight mass spectrometry (SPME-GC × GC-TOFMS) showed that kefir fermented with freeze-dried starter cultures did not change the volatile profile compared to fresh cultures.ConclusionThese findings indicate that freeze-dried starter cultures consisting of traditional kefir microorganisms are able to recreate the fresh starter culture version of this product. This provides encouraging evidence for the development of commercially viable starter cultures that are capable of recreating traditional functional fermented foods.